Testing baby : the transformation of newborn screening, parenting, and policy making - Grob, Rachel, 1966- (Critical issues in health and medicine., 2011)
Testing Baby is the first book to draw on parents' experiences with newborn screening in order to examine its far-reaching sociological consequences. Newborn screening occurs almost always without parents' consent and often without their knowledge or understanding, yet it has the power to alter such things as family dynamics at the household level, the context of parenting, the way we manage disease identity, and how parents' interests are understood and solicited in policy debates. Rachel Grob's cautionary tale explores the powerful ways that parents' narratives.